Extrusion Bioprinting of Scaffolds for Tissue Engineering Applications - Chen, Daniel X. B.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book introduces readers to the theory and practice of extrusion bioprinting of scaffolds for tissue engineering applications. The author emphasizes the fundamentals and practical applications of extrusion bioprinting to scaffold fabrication, in a manner particularly suitable for those who wish to master the subject matter and apply it to real tissue engineering applications. Readers will learn to design, fabricate, and characterize tissue scaffolds to be created by means of extrusion bio-printing technology. Provides a comprehensive introduction to extrusion bioprinting technology; Discusses methods and techniques for the design, fabrication, and characterization of scaffolds based on extrusion bio-printing technology; Includes case studies of print and characterizing scaffolds for tissue engineering applications; Enables readers to fabricate and characterize scaffolds with living cells for tissue engineering applications.
Extrusion Bioprinting of Scaffolds: an Introduction -- Scaffold Design for Bioprinting -- Biomaterials for Bioprinting -- Mechanical Properties of Native Tissues and Scaffolds -- Preparation of Scaffold Solutions and Characterization of Their Flow-Behavior -- Extrusion Bioprinting of Scaffolds -- Bioprinting Vascular Networks in Scaffolds.
Keywords: Biomedical engineering; Biomaterials; Biotechnology; Regenerative medicine; Biomedical Engineering and Bioengineering; Biomaterials; Biotechnology; Regenerative Medicine and Tissue Engineering